THE INFLUENCE OF THE JARIMATIKA METHOD ON THE INTEREST IN LEARNING MATHEMATICS AMONG THIRD-GRADE STUDENTS AT MI NW TAMPIH - Mardiani Mardiani (Formad English Foundation NTB Jakarta, 2024)
This study was conducted to determine the influence of the Jarimatika method on the interest in learning mathematics among third-grade students at MI NW Tampih. The research used a descriptive quantitative approach, aiming to describe or provide an overview of the object studied through sample or population data as it is. The method used in this study is descriptive with an ex post facto nature. The population of this study consists of all third-grade students at MI NW Tampih. The sample, which serves as the data source, includes all 17 third-grade students, making this a population study. Based on the analysis, it can be concluded that there is a significant relationship between the Jarimatika method and the students' interest in learning mathematics in the third grade at MI NW Tampih. This is evidenced by the product moment calculation, where the obtained r-value is 0.5605. The r-table value for N=17 is 0.482. Therefore, r-calculated > r-table (0.5605 > 0.482). According to the criteria, the r-calculated value (0.5605) falls into the medium category.